2019
DOI: 10.1002/hyp.13414
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall partitioning through a mixed cedar swamp and associated C and N fluxes in Southern Ontario, Canada

Abstract: Partitioning of rainfall through a forest canopy into throughfall, stemflow, and canopy interception is a critical process in the water cycle, and the contact of precipitation with vegetated surfaces leads to increased delivery of solutes to the forest floor. This study investigates the rainfall partitioning over a growing season through a temperate, riparian, mixed coniferous-deciduous cedar swamp, an ecosystem not well studied with respect to this process. Seasonal throughfall, stemflow, and interception wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 66 publications
2
6
3
Order By: Relevance
“…Mean (±standard deviation) flux‐based DOC enrichment ratios observed in this study for sugar maple and yellow birch stemflow relative to incident precipitation (ER S,P = 110 ± 88 and 122 ± 102, respectively) were higher than those observed in a mixed cedar swamp in Ontario (ER S,P = 16 to 68) (Duval, 2019) and higher than those of an evergreen broad leafed stand in Japan (68) (Chen et al., 2019). Mean flux‐based TDN enrichment ratios of stemflow relative to precipitation in this study (range = ER S,P = 8.0 to 16) were more similar to those reported by Duval (2019) (4.2–16). Stemflow ER S,P for total nitrogen from a variety of research sites globally ranged from three in a tropical Costa Rican lowland rainforest to 44 in a South African Eucalyptus plantation (Levia and Germer, 2015).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Mean (±standard deviation) flux‐based DOC enrichment ratios observed in this study for sugar maple and yellow birch stemflow relative to incident precipitation (ER S,P = 110 ± 88 and 122 ± 102, respectively) were higher than those observed in a mixed cedar swamp in Ontario (ER S,P = 16 to 68) (Duval, 2019) and higher than those of an evergreen broad leafed stand in Japan (68) (Chen et al., 2019). Mean flux‐based TDN enrichment ratios of stemflow relative to precipitation in this study (range = ER S,P = 8.0 to 16) were more similar to those reported by Duval (2019) (4.2–16). Stemflow ER S,P for total nitrogen from a variety of research sites globally ranged from three in a tropical Costa Rican lowland rainforest to 44 in a South African Eucalyptus plantation (Levia and Germer, 2015).…”
Section: Discussionsupporting
confidence: 88%
“…Low variability of the exponential decay model slopes ( c in Equation ) fit to DOC and TDN concentrations for both throughfall and stemflow suggests a shared process (e.g., dilution by rainfall) drives the variability in DOC export (Figure 5). Exponential decay slopes modeled in this study (∼0.07 mm −1 ) are higher than those reported by Duval (2019) (∼0.03 mm −1 ) but lower than those reported in Van Stan et al. (2017) (∼0.1 mm −1 ).…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…Shading interception rate (α) depends on the type of forest, shade density, and leaf surface width (Wang et al, 2012). In studies, the shading interception rate was found between 18.33% and 26.38% (McDowell et al, 2020;Duval, 2019;Biao et al, 2010). It was stated that this ratio is between 23.50% and 26.38% in pine species and forest areas with mixed trees.…”
Section: Methodsmentioning
confidence: 98%